Food and beverages: Sevenlicious Cafe / Muhamad Nabil Ahmad Sukri ... [ et al.] - Ahmad Sukri, Muhamad Nabil; Mohd Kadir, Nor Sakinah; Mohd Saad, Nur Amalina; Ahmad Samri, Syaza Damia; Naza Badi, Zariq Nazaruddin (2019)
Case study is a study of a business or an organization in a way that can describe on how, as a client, that business or that organization benefited by implementing the preferred and correct products or solutions. Therefore, the case study has been conducted towards Sevenlicious Cafe, which is located in Shah Alam, Selangor. This food and beverages (F&B) business is a newly developed business that is currently being run by an experienced businessman, Lar. Dzarul Hardy Azwar. Despite that, there will be no perfect company with no issues or problem. Thus, difficulties to offer a quick service as a lot of customers waiting in line since they usually come in groups is one of the major problem that occurred in Seventeen Cafe. So that, there are a few alternatives solutions for this problem that suggested for the improvement such as the restaurant should be using iPad POS system which can prevent time-lagging for the customers and Sevenlicious Cafe should make online ordering or reservations as it can help the customers to eliminate the waiting time. So, from both alternative solutions, the best one that has been *' chosen is to offer a drive-through service to the customers as it offer fast service, better menu displays and can easily make quick purchase for the customer. Lastly, by following the SWOT analysis guidance, managed to analyse and discover the strengths, weaknesses, opportunities and threats in Sevenlicious Cafe.